Self-consistent modelling of plasma density increase with radio-frequency heating - Moiseenko, V.Е.; Stadnik, Yu.S.; Lyssoivan, A.I. (Вопросы атомной науки и техники, 2012)
The self-consistent model of the radio-frequency (RF) plasma production in stellarators is described in this work. With this model of plasma production, one can perform calculations for different antenna systems. The selfconsistent model includes the system of the particle and energy balance equations and the boundary problem for the Maxwell’s equations. The numerical calculations of RF plasma production with four-strap antenna in the Uragan-2M stellarator are presented.